Evaluation by Environmental Monitoring of Pesticide Absorption in Farm Workers of 18 Italian Tomato Cultivations. (April 2013) - Basilicata, P.; Simonelli, A.; Silvestre, A.; Lamberti, M.; Pedata, P.; Feola, D.; Acampora, A.; Pieri, M.; Sannolo, N.; Miraglia, N.
Tomato cultivation farms of Southern Italy were investigated in order to evaluate the general working conditions and the levels of exposure of farm workers to pesticides, during the mixing/loading and the application of pesticides on fields. Information on working modalities, personal protective equipment, etc. was collected using a questionnaire. Inhaling and cutaneous exposure levels were measured, and the estimated pesticide total absorbed dose was compared with Admissible Daily Intakes (ADIs). Field treatments were mainly carried out by using sprayers with open cab tractors, and, in 57.9% of cases, the pesticide mixture was manually prepared by mixing pesticides in a pail, often without using gloves (59.5%). The estimated pesticides absorbed doses varied in the range 0.56–2630.31 mg (mean value, 46.9 mg), and 20% of the measured absorbed doses exceeded ADIs. The findings obtained in the 18 examined farms show a worrying situation, suggesting the investigation of many more farms, so that a statistically significant picture of tomato cultivations in Southern Italy could be formed. Besides, the planning of training courses aimed to increase workers consciousness about health risks and how they can be prevented is advisable.